2014
DOI: 10.1073/pnas.1415440111
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of pristine aerosol environments on a polluted planet

Abstract: Significance Uncertainty in aerosol forcing of climate since the preindustrial era hampers efforts to quantify the sensitivity of global temperature to radiative perturbations caused by human activity. Because forcings are referenced to preindustrial conditions, a large part of the uncertainty will be reduced only by accurately defining pristine aerosol conditions before air pollution. We show that pristine conditions should still be observable on a few days per month in many regions of the Earth. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
181
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(197 citation statements)
references
References 54 publications
13
181
2
1
Order By: Relevance
“…Therefore, a direct anthropogenic influence on the marine aerosol upwind of and in the Caribbean, brought on by man-made fires, cannot be completely excluded. This is in line with results reported in Hamilton et al (2014), where it is stated that pristine aerosols (i.e., those free of anthropogenic influence) on Earth are largely only found in the Southern Hemisphere, while these pristine environments are only found temporarily and with a spatially patchy distribution in the Northern Hemisphere. Information on particle composition derived from our data suggests that the majority of particles in the CCN size is made up of sulfates, and these particles mostly originated from new particle formation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, a direct anthropogenic influence on the marine aerosol upwind of and in the Caribbean, brought on by man-made fires, cannot be completely excluded. This is in line with results reported in Hamilton et al (2014), where it is stated that pristine aerosols (i.e., those free of anthropogenic influence) on Earth are largely only found in the Southern Hemisphere, while these pristine environments are only found temporarily and with a spatially patchy distribution in the Northern Hemisphere. Information on particle composition derived from our data suggests that the majority of particles in the CCN size is made up of sulfates, and these particles mostly originated from new particle formation.…”
Section: Discussionsupporting
confidence: 92%
“…Aerosols arriving on Barbados often have been considered clean and/or typical marine due to the incoming air masses being free of anthropogenic influences for thousands of kilometers prior to arrival. But we will show that even this aerosol is not free of continental, and hence possibly anthropogenic, influences, as already suggested by Hamilton et al (2014), who claim that pristine atmospheric aerosols today are found mainly only in the Southern Hemisphere and only very rarely in the Northern Hemisphere.…”
supporting
confidence: 77%
“…Many key portions of the globe remain undersampled, for example, the Southern Ocean, the maritime and continental tropics, much of Asia, and both polar regions. In an effort to replicate preindustrial aerosol−cloud relationships, it is helpful to study those regions of the present-day atmosphere that approximate preindustrial conditions (71). In such regions, clouds are particularly susceptible to small increases in CCN levels (72); the remote Southern Ocean is a prime example.…”
Section: Observations Of Aerosol−cloud Relationshipsmentioning
confidence: 99%
“…These episodes have been defined according to Moran-Zuloaga et al (2017). 1 The question to what extent the Amazonian wet season approximates a pristine and pre-industrial state, which is unaffected by human activities, has been actively debated over the last 30 years (Andreae, 2007;Martin et al, 2010b;Hamilton et al, 2014). Although the wet season is free from major pollution influence, there is evidently a persistent background pollution in varying states of dilution.…”
Section: Aerosol and Ccn Time Series For Representative Wet Season Comentioning
confidence: 99%